DAN plays important compensatory roles in systemic‐to‐pulmonary shunt associated pulmonary arterial hypertension. (27th February 2019) - Meng, Liukun; Liu, Xiaoyan; Teng, Xiao; Yuan, Wen; Duan, Lihua; Meng, Jian; Li, Jun; Zheng, Zhe; Wei, Yingjie; Hu, Shengshou
Abstract: Aim: Proteins mainly expressed in normal lungs and significantly changed in lungs exposed to systemic‐to‐pulmonary shunts might be promising targets for pulmonary arterial hypertension induced by congenital heart diseases (PAH/CHD). This study aimed to investigate the potential role of differential screening‐selected gene aberrative in neuroblastoma (DAN) in PAH/CHD. Methods: PAH was surgically induced by the combined surgery (right pulmonary artery ligation and left cervical systemic‐to‐pulmonary shunt) in Sprague‐Dawley (SD) rats. Exogenous DAN was supplemented by osmotic minipumps. Results: Firstly, DAN was significantly decreased in patients with severe PAH/CHD and negatively correlated with pulmonary hemodynamic indices derived from right cardiac catheterization. Secondly, pulmonary hypertensive status and apparent pulmonary vasculopathies of PAH/CHD were surgically reproduced in SD rats. Real time‐PCR and Western blot analysis revealed that DAN mRNA and protein levels decreased in lungs exposed to systemic‐to‐pulmonary shunts, and immunofluorescence staining found that DAN was highly expressed in pulmonary arteries of normal lungs but seldom detected in severely remodelling pulmonary arteries, furthermore, plasma levels of DAN in shunted‐rats manifested a time‐depended decrease and negatively correlated with pulmonary hemodynamic indices. Thirdly, DAN specially reversed the anti‐proliferative and pro‐apoptotic effects of bone morphogenetic protein 2/4 (BMP2/4) on pulmonary arterial smooth muscle cells via BMP2/4‐BMPR2‐Smad1/5/8‐Id1 signalling pathway. Furthermore, continuous supplementation of exogenous DAN protein increased the extent of shunt‐associated PAH. Conclusion: Compensatory decrease of DAN in hypertensive lungs may retard the deterioration of shunt‐associated PAH, at least in part, by antagonizing BMP signalling pathway. Furthermore, DAN might be a potential biomarker for PAH/CHD.